Metode Punishment Terhadap Moral Siswa - Wasilah Wasilah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
The Punishment method given by the teacher plays an important role in the process of students' moral development. Punishments given by teachers or parents to MTS students Nurul Huda Pakandangan Barat Bluto Sumenep Regency are an unpleasant act that is committed against someone consciously and intentionally to reduce or reduce the occurrence of violations or mistakes. This study aims to determine whether there is an influence between the Punishment Method on student morale at MTs Nurul Huda Pakandangan Barat, and how much influence it has on student morale, and whether this has significance or not. This study uses a quantitative approach, and its nature is causal correlation. Meanwhile, data collection was carried out using questionnaires and documentation techniques. The sampling technique taken was the entire population of the total population of 67 respondents. The processed data is combined using Pearson's Product Moment correlation statistics, to find the relationship between variable X and variable Y. After the researchers conducted research with the title "Punishment Method for Student Morale" with data obtained through questionnaire scores and noble moral values. Then the data is processed through the Product Moment correlation formula, and then the results are matched to the critical price table from the Product Moment correlation, the results of processing the data are supported by the results of the initial interviews. For df = (N-2) = 65 significant 95% of 0.240. Meanwhile, 99% is 0.312. While the results obtained from the calculation of rxy = 0.645. Thus the final conclusion of the researcher is that the Punishment Method has a positive effect on student morale at MTS Nurul Huda Pakandangan Barat Bluto in the Enough category.